Comparing frames, framing comparisons: Greece/EU frames on gender inequality in politics - Maloutas, Maro Pantelidou (The Greek Review of Social Research, 2016)
This article intends to present the main similarities and differences between Greece and the EU in respect to the framing of gender inequality in political decision making as a policy issue, based on the ways that the problem is diagnosed. It also aims at the formulation of a hypothesis which argues that beyond the above similarities and differences, which may tint in a different colour measures and policies showing one case more gender sensitive or more «traditional» than the other, there exists one basic underlying similarity, relative to the conceptualisation of the notion of gender it-self, which frames all gender related policies, but also their comparison. A framing which cannot but show the existence of inherent boundaries to the out-come of gender mainstreaming as a strategy, since the way we conceptualise gender is determining for the degree to which the promoted policies are disruptive or legitimating in the end, of the existing gender order.